Assessing Gonadotropin Receptor Function by Resonance Energy Transfer-Based Assays - Ayoub, Mohammed Akli (Front Endocrinol (Lausanne), 2015)
Gonadotropin receptors belong to the super family of G protein-coupled receptors and mediate the physiological effects of follicle-stimulating hormone (FSHR) and luteinizing hormone (LHR). Their central role in the control of reproductive function has made them the focus of intensive studies. Upon binding to their cognate hormone, they trigger complex signaling and trafficking mechanisms that are tightly regulated in concentration, time, and space. Classical cellular assays often fail to capture all these dynamics. Here, we describe the use of various bioluminescence and fluorescence resonance energy transfer (BRET and FRET) assays to investigate the activation and regulation of FSHR and LHR in real-time, in living cells (i.e., transiently expressed in human embryonic kidney 293 cells). Indeed, the dynamics of hormone-mediated heterotrimeric G protein activation, cyclic adenosine-monophosphate (cAMP) production, calcium release, β-arrestin 2 recruitment, and receptor internalization/recycling was assessed. Kinetics and dose–response analyses confirmed the expected pharmacological and signaling properties of hFSHR and hLHR but revealed interesting characteristics when considering the two major pathways (cAMP and β-arrestin 2) of the two receptors assessed by BRET. Indeed, the EC(50) values were in picomolar range for cAMP production while nanomolar range was observed for β-arrestin 2 recruitment as well as receptor internalization. Interestingly, the predicted receptor occupancy indicates that the maximal G protein activation and cAMP response occur at <10% of receptor occupancy whereas >90% of activated receptors is required to achieve full β-arrestin 2 recruitment and subsequent receptor internalization. The rapid receptor internalization was also followed by a recycling phase. Collectively, our data reveal that β-arrestin-mediated desensitization, internalization, and the subsequent fast recycling of receptors at the plasma membrane may provide a mechanistic ground to the “spare receptor” paradigm. More generally, the novel tools described here will undoubtedly provide the scientific community investigating gonadotropin receptors with powerful means to decipher their pharmacology and signaling with the prospect of pathophysiological and drug discovery applications.